Selinexor in combination with venetoclax and decitabine in patients with refractory myelodysplastic syndrome previously exposed to hypomethylating agents: three case reports - Xiao, Yunshuo; Yang, Kun; Huang, Qiuying; Wei, Changqing; Wei, Manlv; Geng, Zhili; Wu, Hui; Zhou, Tianhong; Yin, Xialoin; Zhou, Yali (Frontiers in Oncology, 2024)
The management of patients with myelodysplastic syndrome (MDS) refractory to hypomethylating agents (HMAs) remains a challenge with few reliably effective treatments. Preclinical studies have shown that the inhibition of the nuclear export protein XPO1 causes nuclear accumulation of p53 and disruption of NF-κB signaling; both of which are relevant targets for MDS. Selinexor is an XPO1 inhibitor with demonstrated efficacy in MDS patients. Herein, we report three patients with MDS refractory to HMAs, however, when selinexor and venetoclax were added to the treatment regimen, the patients achieved a complete response and a significant reduction in spleen size. All patients successfully underwent hematopoietic stem cell transplantation. These cases demonstrate that the combination therapy can achieve CR and significant reductions in spleen size, offering a promising therapeutic option for patients with limited treatment choices. Combination therapy would also offer a potential way for patients to bridge to transplantation. Formal evaluations of this regimen in patients with MDS refractory to HMAs may be meaningful.